HUBUNGAN PIJAT BAYI DENGAN PERKEMBANGAN MOTORIK BAYI USIA 1 – 12 BULAN DI DESA PUNDUNGSARI BULU SUKOHARJO - Rahayu Setyaningsih; Kristiani Eka Prasetyo Wat; Asri Utami (KOSALA : Jurnal Ilmu Kesehatan, 2015)
AbstractIntroduction: Infant massage is a touch therapy oldest known to the public. Infant massage is one of the communication between mother and child is communication through touch. Infant massage has been known to man for a long time and reduced down - generations. Age 1-12 months is a period of rapid growth that is traversed by the child, including motoric development. Infant massage can provide a stimulus to promote weight and to increase motoric development.The purpose: Of this study was to correlate of infant massage and motoric development in infants aged 1-12 months in District Pundungsari Bulu Sukoharjo.The subjects: Were mother with infants aged 1-12 months, in the District Pundungsari. Sampling is done with total sampling technique. They are 33 sample in this research.Methods: This study was a non-experimental studies, correlation approach. Data obtained by the method of questionare, which is mother has filled the questionare about baby massage in infants aged 1-12 months and motoric development. The data have been collected and analyzed by chi square with p= 0.05. The research found that respondents do baby massage with continue and not continue and motoric development found delayed, normal and advance. After the test results obtained chi square p 0.000 to p <0.05, which means Ha accepted and Ho rejected.The conclusion: Of this study is infant massage correlate with motoric development in infants aged 1-12 months in District Pundungsari Bulu Sukoharjo.Keywords: Infant massage, motoric development